Migration paths of cells different origins in the embryonic human heart. - Voloshin, N. A.; Chaykovsky, Yu. B. (Морфологія / Morphologia / Morfologìâ, 2010)
Hearts of human embryos were investigated using immunohistochemical method with antibodies to neurofilaments from 4 to 8 week of prenatal development. It was found that the embryonic human heart there are NF-positive cells, which occupy its territory by two mechanisms: through the migration of intercellular spaces and on the mechanism immersion out of heart cavity. In the second case neurofilaments-positive cells through the endothelium of blood vessels or endocardium immersion into the myocardium or mesenchymal areas. Mesenchyme in the heart contain neurofilament-positive cells, migrating here from both mechanisms. Similar cells have been found by us in the liver of human embryo, beginning at 5 weeks of prenatal development.